Dichotomous Dopaminergic Control of Ventral Pallidum Neurons - Clark, Martin; Bracci, Enrico (Frontiers in Cellular Neuroscience, 2018)
The ventral pallidum (VP) is crucially involved in reward processing. Dopaminergic afferents reach the VP from the ventral tegmental area. Recent in vivo studies suggest dopamine application increase the firing in the VP. However, little is known about the cellular effects of dopamine within the VP. We aimed to address this paucity of data using brain slices containing the VP and multi-electrode array recordings. Dopamine significantly affected firing in 86 % of spontaneously active VP neurons. Among the affected neurons, 84 % were excited, while 16 % were inhibited. The selective D1-like receptor agonist SKF81297 also had modulatory effects on the majority of VP neurons, but its effects were universally excitatory. On the other hand, the D2-like receptor agonist quinpirole had modulatory effects on 87 % of VP neurons studied. It caused significant inhibitory effects in 33 % of the cases and excitatory effects in the remaining 67 %. The effects of D1-like receptor activation were presynaptic as blocking synaptic transmission with low Ca2+ abolished the effects of SKF81297 application. Furthermore, SKF81297 effects were abolished by blocking ionotropic glutamate receptors, suggesting that D1-like receptors boost glutamate release, which in turn excites VP neurons through postsynaptic glutamate receptors. Effects caused by D2-like receptor activation were found to involve pre and postsynaptic mechanisms, as low Ca2+ abolished the excitatory effects of quinpirole but not the inhibitory ones. Increases in firing frequency to quinpirole application were abolished by a group 2/3 mGluR antagonist, suggesting that D2-like receptors cause presynaptic inhibition of glutamate release, resulting in reduced postsynaptic activation of inhibitory mGluRs. Conversely, the inhibitory effects of quinpirole persisted in low Ca2+ and therefore can be attributed to postsynaptic D2-like receptor activation. VP neurons excited by dopamine ha shorter spike half-widths and are excited by D1-like receptors (presynaptically) and by D2-like receptors (postsynaptically). VP neurons inhibited by dopamine have longer spike half-widths and while D1-like receptor activation has a presynaptic excitatory influence on them, D2-like receptor activation has a postsynaptic inhibitory effect that prevails, on balance. These data provide novel insights into the cellular mechanisms by which dopamine controls information processing within the VP.